Economics - McConnell, Campbell R.
This new AP edition of McConnell, Brue, and Flynn's Economics: Principles, Problems, and Policies continues to be innovative while teaching students in a clear, unbiased way. This edition builds upon the tradition of leadership by sticking to 3 main goals: Help the beginning student master the principles essential for understanding the economizing problem, specific economic issues, and the policy alternatives; help the student understand and apply the economic perspective and reason accurately and objectively about economic matters; and promote a lasting student interest in economics and the economy. The authors have also focused on pedagogy, making the book even more accessible for high school AP students with additional real-world examples, case studies, and analogies to help students see how economic theory manifests in the world around them